Thermal Degradation Study of Hydrogel Nanocomposites Based on Polyacrylamide and Nanosilica Used for Conformance Control and Water Shutoff - Aleksey Telin; Farit Safarov; Ravil Yakubov; Ekaterina Gusarova; Artem Pavlik; Lyubov Lenchenkova; Vladimir Dokichev (Gels)
The application of nanocomposites based on polyacrylamide hydrogels as well as silica nanoparticles in various tasks related to the petroleum industry has been rapidly developing in the last 10–15 years. Analysis of the literature has shown that the introduction of nanoparticles into hydrogels significantly increases their structural and mechanical characteristics and improves their thermal stability. Nanocomposites based on hydrogels are used in different technological processes of oil production: for conformance control, water shutoff in production wells, and well killing with loss circulation control. In all these processes, hydrogels crosslinked with different crosslinkers are used, with the addition of different amounts of nanoparticles. The highest nanoparticle content, from 5 to 9 wt%, was observed in hydrogels for well killing. This is explained by the fact that the volumes of injection of block packs are counted only in tens of cubic meters, and for the sake of trouble-free workover, it is very important to preserve the structural and mechanical properties of block packs during the entire repair of the well. For water shutoff, the volumes of nanocomposite injection, depending on the well design, are from 50 to 150 m3. For conformance control, it is required to inject from one to several thousand cubic meters of hydrogel with nanoparticles. Naturally, for such operations, service companies try to select compositions with the minimum required nanoparticle content, which would ensure injection efficiency but at the same time would not lose economic attractiveness. The aim of the present work is to develop formulations of nanocomposites with increased structural and mechanical characteristics based on hydrogels made of partially hydrolyzed polyacrylamide crosslinked with resorcinol and paraform, with the addition of commercially available nanosilica, as well as to study their thermal degradation, which is necessary to predict the lifetime of gel shields in reservoir conditions. Hydrogels with additives of pyrogenic (HCSIL200, HCSIL300, RX380) and hydrated (white carbon black grades: ‘BS-50’, ‘BS-120 NU’, ‘BS-120 U’) nanosilica have been studied. The best samples in terms of their structural and mechanical properties have been established: nanocomposites with HCSIL200, HCSIL300, and BS-120 NU. The addition of hydrophilic nanosilica HCSIL200 in the amount of 0.4 wt% to a hydrogel consisting of partially hydrolyzed polyacrylamide (1%), resorcinol (0.04%), and paraform (0.09%) increased its elastic modulus by almost two times and its USS by almost three times. The thermal degradation of hydrogels was studied at 140 °C, and the experimental time was converted to the exposure time at 80 °C using Van’t Hoff’s rule. It was found that the nanocomposite with HCSIL200 retains its properties at a satisfactory level for 19 months. Filtration studies on water-saturated fractured reservoir models showed that the residual resistance factor and selectivity of the effect of nanocomposites with HCSIL200 on fractures are very high (226.4 and 91.6 for fracture with an opening of 0.05 cm and 11.0 for porous medium with a permeability of 332.3 mD). The selectivity of the isolating action on fractured intervals of the porous formation was noted.